Correction: A vessel subtype beneficial for osteogenesis enhanced by strontium-doped sodium titanate nanorods by modulating macrophage polarization. Issue 34 (20th August 2020) - Guo, Shuo; Yu, Dongmei; Xiao, Xin; Liu, Wenwen; Wu, Zhigang; Shi, Lei; Zhao, Quanming; Yang, Di; Lu, Yajie; Wei, Xinghui; Tang, Zhen; Wang, Ning; et al.
Abstract : Correction for 'A vessel subtype beneficial for osteogenesis enhanced by strontium-doped sodium titanate nanorods by modulating macrophage polarization' by Shuo Guo et al., J. Mater. Chem. B, 2020, 8, 6048–6058. DOI: ; 10.1039/D0TB00282H .